Capacidades e práticas de líderes Lean de nível operacional e efeitos na implementação de ferramentas: survey em empresas industriais - Simões, Julianita Maria Scaranello (Universidade Federal de São Carlos, 2021)
Lean leadership is considered a fundamental factor for the effective implementation of Lean Production System (LPS). However, Lean leadership studies, especially for Lean operational-level leadership, remain limited to the capacities and practices of Lean leadership that provide effective implementation of LPS tools in organizations. This thesis aims to analyze the relationship between capacities and practices of front-line Lean leaders and the implementation of Lean tools in large manufacturing companies. A survey was conducted in large manufacturing companies in the State of São Paulo, with Lean programs implemented for at least 5 years. A total of 103 questionnaires were collected, of which 99 were considered valid. The data were analyzed by Structural Equations Modeling (PLS-SEM) through SmartPLS 3 software. A positive, significant and direct relationship was observed among the capacities of front-line Lean leaders, leadership practices and implementation of LPS tools on the shop floor. From a management point of view, it can also be noted that investing in the Lean leaders' capacities development provide better operationalization of leadership practices which in turn allow a better implementation of LPS tools on the shop floor of organizations. From the theoretical point of view, it was observed relevant expansion of the field of knowledge about front-line Lean leaders with the proposition of a replicable model based on specific capacities and practices that contribute to the implementation of Lean tools.
Front-line Lean leader capacities and practices and their effects on implementing tools: survey of industrial companies
Keywords: Capacidades de líderes Lean; Práticas de liderança no SPL; Implementação de ferramentas do SPL; SPL - Sistema de Produção Lean; Liderança Lean de nível operacional; Lean leadership capacities; Leadership practices in LPS; Implementation of LPS tools; LPS - Lean Production System; Front-line Lean leaders; ENGENHARIAS::ENGENHARIA DE PRODUCAO::GERENCIA DE PRODUCAO